Provisions of Indonesian Medical Discipline Sanctions to Protect The Rights of Patient be Reviewed From Theprinciple of The Establishment of Legislation - Wellem Hendra Balubun; Valentinus Suroto; Edi Sumarwanto (Universitas Katolik Soegijapranata Semarang, 2018)
ABSTRACT: This study aims to determine, first: the effectiveness of the provisions of medical discipline sanctions for doctors and dentists to protect the rights of patients be reviewed from the principles of the establishment of legislation. Second: the mechanism of sanctioning Medical Discipline for doctors and dentists This research uses a normative juridical approach. The specification of this research is descriptive analytical. The type of data used is secondary data obtained through literature study and then analyzed qualitatively and drawn conclusions with deductive and inductive thought method. The results of this study show that first: the provisions of Indonesian medical discipline sanction based on the principle of Clarity of Purpose, medical discipline sanction is established with a clear purpose that is as a form of guidance and supervision of medical practice in Indonesia. Based on the principle of Implementation, medical discipline sanction is said to be implemented because it has been regulated in the Regulation of KKI (Perkonsil) Number 50 of 2017 on the Procedures for Handling Cases of Alleged Violations of Doctor and Dentist Discipline. Based on the principles of Usability and Useful, by looking at the background of the formation of medical disciplinary sanctions which, among others, the high number of disciplinary violations, then disciplinary sanctions are really needed and yet not beneficial to the community. The principle of Clarity Formulation, the formulation of medical discipline sanction is clear and not multitasker so it can be easily understood. From the results of this analysis can be said that the provisions of disciplinary sanctions are effective. Secondly, the mechanism of sanction is set in number 50 of 2017 on the Procedures for Handling the Case of Alleged Discipline of Doctor and Dentist, which regulates the procedure and also the authority in the imposition of sanctions and the implementation of sanctions. The mechanism is the process of imposition of sanctions is the authority of MKDKI while the implementation of the decision of sanctions unification is the authority of KKI.